2009
DOI: 10.1177/1524838009339757
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment, Intervening Variables, and Adult Psychological Difficulties in Women

Abstract: This article reviews the complex relationship between child maltreatment and later psychosocial difficulties among adult women. Specifically addressed are (a) the various forms of childhood maltreatment, (b) the range of potential long-term psychological outcomes, and (c) important contextual variables that mediate or add to these maltreatment-symptom relationships. Among the latter are characteristics of the abuse and/or neglect; effects of impaired parental functioning; premaltreatment and postmaltreatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 118 publications
10
116
0
3
Order By: Relevance
“…This corroborates many past studies that have also found the debilitating effect of childhood abuse and its relationship to internalizing and externalizing behavior problems including NSSI (Brausch and Holaday, 2015;Gratz, 2006;Smith et al, 2014). Scholars have tried to explain the underlying mechanisms by which childhood abuse may relate to long-term emotional dysfunction and have observed that adolescents with a history of childhood abuse are likely to have trouble regulating their affect and emotions and experience a sense of insecurity (Briere and Jordan, 2009), which consequently leads to NSSI (Santangelo et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…This corroborates many past studies that have also found the debilitating effect of childhood abuse and its relationship to internalizing and externalizing behavior problems including NSSI (Brausch and Holaday, 2015;Gratz, 2006;Smith et al, 2014). Scholars have tried to explain the underlying mechanisms by which childhood abuse may relate to long-term emotional dysfunction and have observed that adolescents with a history of childhood abuse are likely to have trouble regulating their affect and emotions and experience a sense of insecurity (Briere and Jordan, 2009), which consequently leads to NSSI (Santangelo et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Žmonės, dažniau naudojantys situacijos pervertinimą, lengviau įveikia stresą keliančius išgyvenimus ir sėkmingiau pagerina savo nuotaiką, tuo tarpu emocijas slopinantys individai patiria mažiau teigiamo afekto ir mažiau sėkmingai geba pagerinti savo nuotaiką (8,9). Randasi tyrimų, rodančių, kad smurto patyrimas vaikystėje siejasi prastesniais emocijų reguliacijos gebėjimų ir neefektyvių emocijų reguliacijos strategijų naudojimu suaugystėje (10)(11)(12), tačiau mažiau žinoma apie šiuos ryšius ankstyvosios paauglystės amžiuje, kai emociniai ir kognityviniai paauglystės pokyčiai dar tik prasideda. Skirtingi tyrimai rodo, kad prasta emocijų reguliacija vienaip ar kitaip siejasi su skirtingais psichikos sveikatos sunkumais (3).…”
Section: Vilniaus Universiteto Medicinos Fakulteto Psichiatrijos Klinikaunclassified
“…Cependant, il y a tout lieu de penser qu'un processus indirect se produirait. En effet, les victimes de victimisations fréquentes pendant l'enfance souffrent de conséquences négatives cognitives, affectives et relationnelles sur le long terme (Briere et Jordan, 2009). Il est donc probable que l'enfance des codélinquantes, à travers les expériences de négligence et la qualité des relations avec les parents, et notamment avec la mère, ait joué un rôle dans le développement de leurs difficultés personnelles, sociales et émotionnelles.…”
Section: Trajectoires De Vieunclassified